Divergence in physiological factors affecting swimming performance between anadromous and resident populations of brook charr Salvelinus fontinalis. Issue 5 (19th March 2017) - Crespel, A.; Dupont‐Prinet, A.; Bernatchez, L.; Claireaux, G.; Tremblay, R.; Audet, C.
Abstract : In this study, an anadromous strain (L) and a freshwater‐resident (R) strain of brook charr Salvelinus fontinalis as well as their reciprocal hybrids, were reared in a common environment and submitted to swimming tests combined with salinity challenges. The critical swimming speeds ( U crit ) of the different crosses were measured in both fresh (FW) and salt water (SW) and the variations in several physiological traits (osmotic, energetic and metabolic capacities) that are predicted to influence swimming performance were documented. Anadromous and resident fish reached the same U crit in both FW and SW, with U crit being 14% lower in SW compared with FW. The strains, however, seemed to use different underlying strategies: the anadromous strain relied on its streamlined body shape and higher osmoregulatory capacity, while the resident strain had greater citrate synthase (FW) and lactate dehydrogenase (FW, SW) capacity and either greater initial stores or more efficient use of liver (FW, SW) and muscle (FW) glycogen during exercise. Compared with R♀ L♂ hybrids, L♀ R♂ hybrids had a 20% lower swimming speed, which was associated with a 24% smaller cardio‐somatic index and higher physiological costs. Thus swimming performance depends on cross direction ( i.e. which parental line was used as dam or sire). The study thus suggests that divergent physiological factors between anadromous and resident S. fontinalis may result in similar swimming capacities that are adapted to their respective lifestyles.